Natureza e ser humano: uma questão moral. - Idete Teles dos Santos (Nepan editor, 2015)
The proposal is to reflect the relationship between man and the environment from philosophical foundations of bioethics. The aim is to show that not only can offer moral arguments for the preservation of nature based on the man’s well-being, but also there is the possibility of arguments in the nature not only as an instrumental value, but a value intrinsic. That argument will primarily theoretical basis to work Practical Ethics (1979) by Peter Singer. Moreover, from the theoretical framework mentioned, will offer arguments so that we can reflect on the singular, particular and immediate, such as biopiracy in the Amazon. One conclusion that this proposed theoretical discussion will expose is that, often, the narrow vision of viral and absolutely focused on the financial gain man, makes it at least immoral before nature and so one of the consequences of this attitude, it is his destruction.